The changing influence of host genetics on the leaf fungal microbiome throughout plant development. - Talia L Karasov; Derek S Lundberg (PLoS Biology)
Host genetics and the environment influence which fungal microbes colonize a plant. A new study in PLOS Biology finds that the relative influence of these factors changes throughout the development of the biofuel crop switchgrass growing in field settings.